ROAD TRAFFIC ACCIDENTS CASUALTIES IN THE NORTH OF JORDAN: AN EPIDEMIOLOGICAL STUDY - Ali M. Shotar; Sukaina A. Alzyoud; Jamal Obeidat; Khalid A. Alhawamdeh (European Scientific Journal, ESJ, 2014)
Road Traffic Accidents are considered to be one of the leading causes of death and injuries worldwide. In recent years as many as 50 million people are injured or disabled by road traffic accidents every year. Road traffic accidents impose a burden on countries by costing up to 4% of their Gross National Product. Therefore, the purpose of this study was to determine the prevalence of injuries resulted from road traffic accidents in the North region of Jordan in the years 2003 – 2007. A retrospective design was used to review all RTA incident report located at the Northern Forensic Medicine Teaching Center. Reports were reviewed for age, gender, accident detailed report (such as, date, cause, geographical location, injuries). A total of 7918 accidents were reported between the years 2003 to 2007. Male Jordanians were more involved in traffic accidents than females. Almost one third (31.8%) of accidents occurred during the weekend. Running over pedestrian accounted for (70.9%) of all reported accidents. In addition, (49%) of run over incidents were among children, adolescents, and young adults. Wounds, fractures, and pain were the most prevalent consequences of road traffic accidents. This study is the first critical step towards establishing a base line data of road traffic accidents injuries in Jordan. Reviewing and evaluating existing policies of traffic safety would be the next logical step. Additionally, establishing a team of health care and other professionals to work on developing new traffic safety polices to ensure road safety.